Nannocystin A: an Elongation Factor 1 Inhibitor from Myxobacteria with Differential Anti‐Cancer Properties1. (14th July 2015) - Krastel, Philipp; Roggo, Silvio; Schirle, Markus; Ross, Nathan T.; Perruccio, Francesca; Aspesi, Peter; Aust, Thomas; Buntin, Kathrin; Estoppey, David; Liechty, Brigitta; Mapa, Felipa; Memmert, Klaus; et al.
Abstract Cultivation of myxobacteria of the Nannocystis genus led to the isolation and structure elucidation of a class of novel cyclic lactone inhibitors of elongation factor 1. Whole genome sequence analysis and annotation enabled identification of the putative biosynthetic cluster and synthesis process. In biological assays the compounds displayed anti‐fungal and cytotoxic activity. Combined genetic and proteomic approaches identified the eukaryotic translation elongation factor 1α (EF‐1α) as the primary target for this compound class. Nannocystin A (1) displayed differential activity across various cancer cell lines and EEF1A1 expression levels appear to be the main differentiating factor. Biochemical and genetic evidence support an overlapping binding site of 1 with the anti‐cancer compound didemnin B on EF‐1α. This myxobacterial chemotype thus offers an interesting starting point for further investigations of the potential of therapeutics targeting elongation factor 1.